Making Healthful Food Choices: The Influence of Health Claims and Nutrition Information on Consumers’ Evaluations of Packaged Food Products and Restaurant Menu Items - Kozup, John C.; Creyer, Elizabeth H.; Burton, Scot (Journal of Marketing, 2003)
The authors report the results of three experiments that address the effects of health claims and nutrition information placed on restaurant menus and packaged food labels. The results indicate that when favorable nutrition information or health claims are presented, consumers have more favorable attitudes toward the product, nutrition attitudes, and purchase intentions, and they perceive risks of heart disease and stroke to be lower. The nutritional context in which a restaurant menu item is presented moderates the effects of both nutrition information and a health claim on consumer evaluations, which suggests that alternative (i.e., nontarget) menu items serve as a frame of reference against which the target menu item is evaluated.